Animating the archive: the trial and testimony of a Sufi saint. (February 2016) - De Jong, Ferdinand
Abstract: In 1895 the colonial administration of Senegal sentenced Sheikh Amadu Bamba to exile for stirring anti‐colonial disobedience. At his trial, Bamba allegedly recited a prayer in defiance of the French authorities. Although there is no archival record to prove that the prayer was recited, since the 1970s Bamba's disciples have flocked to the former seat of colonial power to commemorate his act of resistance; their testimony has displaced the authority of the colonial archive and imagines a decolonial utopia in archival absence. This article examines how their prayer subverts the colonial archive, while it remains entangled in its substrate.